Associations of anthropometric cardiometabolic risk factors and leg fat accumulation in children and adolescents from Poland. Issue 12 (6th September 2022) - Żegleń, Magdalena; Kryst, Łukasz; Kowal, Małgorzata; Woronkowicz, Agnieszka
Abstract: Objectives: To analyze the correlation between anthropometric cardiometabolic risk factors with calf adiposity in 4–16‐year‐olds from Poland. Methods: Three thousand seventy‐six persons (1568 girls and 1508 boys) were examined. Analyzed characteristics included body height, waist, hips and neck circumferences, body weight, six skinfolds. The following were calculated: body mass index (BMI), waist‐to‐hips ratio (WHR), the sum of all skinfolds, and the sum of skinfolds on the waist area. Results: The relationship between the calf skinfold and the rest of the characteristics was estimated using multiple regression. There was a negative relationship between calf adiposity and fat tissue accumulated around the waist and the BMI (in some groups). This suggests that participants with greater calf adiposity had lower waist adiposity and BMI than those with less fat tissue on the lower limb. Conclusion: Persons with higher calf adiposity may have a lower cardiometabolic risk. This observation is significant because cardiovascular risk factors can persist from childhood into adulthood. Additionally, cardiovascular issues have numerous medical consequences but also socio‐economic ones, thus they can affect individuals and be a burden on public health.